Macro level geoarbitrage and digital nomad policymaking in Portugal - Gaspar, S.; Hannonen, O. (Tourism Geographies, 2026)
Portugal has become one of the most popular countries for digital nomadism in Europe, with Lisbon being a top-rated destination. The global digital nomad hotspots are usually more affordable destinations in which people can live better with their salaries, escaping the high cost of living in Western countries. As such, digital nomads, similar to other types of lifestyle movers, engage in geoarbitrage – the utilization of opportunities for affordable costs of living in foreigner destinations. In Portugal, governmental policies have been developing favorable conditions for these types of travelers. The launch of the digital nomad visa to attract an even greater number of digital nomads supports the growth of this social phenomenon. The aim of this paper is to examine the ways Portuguese government policies are driven by the logic of geoarbitrage, targeting affluent visitors or migrants. Despite the growing relevance of these developments, a comprehensive understanding of how geoarbitrage is constructed and practiced through public policies remains underexplored. This article addresses this gap by exploring the interrelationship between digital nomad visas and geoarbitrage practiced at an institutional level by the Portuguese government. The focus is on the recent Digital Nomad Visa (D8) as well as other residence permits such as the D7 visa previously used by digital nomads. The study shows a pathway of digital nomadism in Portugal from 2007 to the present that has been shaped by strategic policy development of the national government and targeted initiatives like the Digital Nomad Village in Madeira. Moreover, the analysis demonstrates the ways the Portuguese government enacted a geoarbitrage strategy envisioning a logic of immigration of wealthy and highly skilled digital nomads.